Idosos de Veranópolis : suas leituras em narrativas do presente - Boff, Rolcinéia Rodrigues (2015)
Elderly from Veranópolis: readings from the past in narratives in the present is characterized as a qualitative research, and as a case study as well, developed on the basis of reading stories featuring eight participants in the Projeto Veranópolis, which binds studies regarding human aging to quality of life in a town located in the mountains of Rio Grande do Sul state known as the Land of Longevity. This research aims to record the stories of experiences and findings of the subjects involved in this study in their childhood and their youth related to reading, in the town of Veranópolis. The research problem consists of the question: How is it possible to identify the literary and non-literary materials which were part of the reading formation of the target audience until the middle of the XX century? To this end, the main theoretical basis stands out as the records of elderly memories (BOSI, 1987, 2003), the history of reading (MANGUEL, 1999), and the collective memory (HALBWACHS, 2006). The data analysis was conducted in three parts: first an analysis of the narratives, followed by the analysis of the accessed books: according to their sources of origin as well as categorization of the types of reading, individually considering each of the book sources. Regarding the interviews, the research brings some reflections on the language and the legitimacy for the speech (CHARAUDEAU, 2008), on the marks of narrative categories, identifying the image of the narrator and the image of the reader (BARTHES,2011), and the participation of the individual in their culture (LARAIA, 2006)